SOME REFLECTIONS ON THE BOOK: “LOS PRINCIPIOS COOPERATIVOS Y SU INCIDENCIA EN EL RÉGIMEN LEGAL Y FISCAL DE LAS COOPERATIVAS [THE COOPERATIVE PRINCIPLES AND THEIR IMPACT ON THE LEGAL AND TAX REGIME OF COOPERATIVES]” - Vargas, Ana Montiel (International Journal of Cooperative Law, 2024)
This work, edited by Professors Marina Aguilar Rubio and Carlos Vargas Vasserot and coordinated by Professor Daniel Hernández Cáceres, all from the University of Almería, is an indispensable read for anyone interested in the legal framework of cooperatives. It is a true treatise on Cooperative Law, consisting of over eight hundred pages and twenty-nine chapters, which bring together experts from various universities and countries across different areas of knowledge. It includes contributions from twenty authors, all leading specialists in the field and researchers with an international and interdisciplinary approach.